Analysis Feasibility Of Farming Ground Water Spinach (Ipomoea Reptans Poir) - Annisa Az Azzahra; Slamet Abadi; Ekalia Yusiana (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to analyze the feasibility of land spinach farming in Sukarukun Village, Sukatani District, Bekasi Regency, to understand the profitability for farming families. Methodology: The study employed a saturated sample method with a population of 30 individuals. Data analysis included total cost analysis, revenue, income, R/C ratio, and Break Even Point (BEP). Results: The results showed that the average total cost was IDR 52,448,625 per year, revenue was IDR 75,600,000 per year, and income was IDR 23,151,375 per year. The R/C ratio was 1.4, indicating that the farming business is feasible. The BEP for production was 3,108 kg, BEP for price was IDR 4,162 per kg, and BEP for revenue was IDR 18,653,718. Findings: The study found that land spinach farming in the study area is profitable and feasible, as indicated by the R/C ratio and BEP calculations. Novelty: This research provides new insights into the economic feasibility of land spinach farming, contributing valuable information for farmers and stakeholders in agricultural planning. Originality: The study offers a detailed economic analysis of land spinach farming, highlighting key metrics such as total cost, revenue, income, R/C ratio, and BEP, which are essential for assessing farming viability. Conclusions: Land spinach farming in Sukarukun Village is economically feasible with a favorable R/C ratio and manageable BEP, making it a viable agricultural activity for local farmers. Type of Paper: Empirical Research Artikel Keywords: Farming Cost; Land Spinach; Feasibility; Revenue; Income